2022
DOI: 10.3389/fncel.2022.809917
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional and Post-translational Modifications of Primary Cilia: How to Fine Tune Your Neuronal Antenna

Abstract: Primary cilia direct cellular signaling events during brain development and neuronal differentiation. The primary cilium is a dynamic organelle formed in a multistep process termed ciliogenesis that is tightly coordinated with the cell cycle. Genetic alterations, such as ciliary gene mutations, and epigenetic alterations, such as post-translational modifications and RNA processing of cilia related factors, give rise to human neuronal disorders and brain tumors such as glioblastoma and medulloblastoma. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 144 publications
(172 reference statements)
0
10
0
Order By: Relevance
“…Similarly, mRNAs that are no longer needed can be readily shuttled away in a translationally-suppressed condition until they are required again, or destroyed. P-bodies, cytoplasmic entities that participate in mRNA processing and degradation and share components with stress granules, appear to co-localize with centrosomes (Aizer & Shav-Tal, 2008) or ciliary basal bodies (Rocha & Prinos, 2022). Notably, P-bodies have also been found to include centriolar satellite proteins such as CEP192, OFD1, PCM1, and CEP131.…”
Section: Delivering the Message: Rna And Translation At Centrosomesmentioning
confidence: 99%
“…Similarly, mRNAs that are no longer needed can be readily shuttled away in a translationally-suppressed condition until they are required again, or destroyed. P-bodies, cytoplasmic entities that participate in mRNA processing and degradation and share components with stress granules, appear to co-localize with centrosomes (Aizer & Shav-Tal, 2008) or ciliary basal bodies (Rocha & Prinos, 2022). Notably, P-bodies have also been found to include centriolar satellite proteins such as CEP192, OFD1, PCM1, and CEP131.…”
Section: Delivering the Message: Rna And Translation At Centrosomesmentioning
confidence: 99%
“…Future studies could investigate the molecular mechanisms behind how OGN levels regulate cilia length, and whether primary cilia transduce different signals at different stages of differentiation. Interestingly, the primary cilium may also facilitate cell-cell communication functions in addition to its role as signal hub to transduce signals [63,67]. Our immunostaining results showed that neuronal cilia form clusters (Figure 2C, Day 55), which possibly allows for cell-cell communication.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to their importance on differentiated neurons, primary cilia also play crucial roles during brain development through the transduction of important signaling pathways, such as Wnt and Shh signaling [63]. Primary cilia are required for the differentiation of neural progenitors and neural stems cells into multiple types of brain cells [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Resembling the noncanonical initiation of the Notch pathway, the later activation of Hh signaling can be categorized into three kinds [40]. Nevertheless, contrary to Notch and other embryonic signaling pathways, the Hh signaling pathway is extremely dependent on the primary cilium [43], a single organelle, with the composition of vital signaling components varying in distribution across the cilium depending on whether Hh signaling is switched on or off [44][45][46].…”
Section: Introductionmentioning
confidence: 99%